REPRESENTASI JEJARING PATRIARKI DALAM NOVEL GOD DIES BY THE NILE KARYA NAWAL EL SAADAWI - Asmarani, Ratna (Faculty of Humanities, Diponegoro University, 2013)
ABSTRACT The purpose of this paper is to analyze the representation of the patriarchal web in Nawal El Saadawi’s novel entitled God Dies by the Nile. In order to do that, feminism is used as the frame of analysis focusing on the concepts of patriarchy. The result shows that the patriarchal web is supported by several males with various powerful positions legalizing many ways to achieve their wicked purposes especially to young beautiful females and to other weak people in general. Keywords: patriarchal web, feminism, patriarchy, males, females.